405 Real-life response to standard of care in advanced ovarian cancer – an observational multi-national cohort study (RESPONSE). (4th December 2020) - Marth, Christian; Lassus, Heini; Lindemann, Kristina; Nieuwenhuyen, Els Van; Ekmann-Gade, Anne Weng; Hansen, Jesper; Andersen, Klaus Kaae; Korach, Jacob
Abstract : Introduction/Background: Recent randomized clinical trials have demonstrated convincing effects of integrating PARP inhibitors (PARPi) and combination of PARPi + bevacizumab (anti-VEGF) into first line (1L) treatment of selected groups of advanced stage ovarian cancer (OC) patients. However, it remains unclear to which extent eligibility of PARPi treatment translates into a real-world setting, where the impact of patient heterogeneity and differences in national clinical practices may influence the potential for PARPi treatment. The aim of this study is to describe treatment strategies and outcomes of advanced OC; and to estimate the proportion of patients potentially eligible for 1L PARPi maintenance therapy and for concomitant anti-VEGF treatment practice using observational data in a multi-national setting (RESPONSE). Methodology: This international, multi-centre, observational study, includes real-world data on diagnostic work-up, standard of care, clinical outcomes and treatment for around 1000 patients with advanced OC (≥120 patients/country). Last index date is 1st April 2018, ensuring at least 20 months of follow-up. Potential PARPi eligibility is defined as having no macroscopic residual disease (<1 cm) following upfront surgery and/or having a clinical complete response/partial response (CR/PR) following completion of 1L chemotherapy according to the label. Eligibility for PARPi treatment will be analysed prospectively by time-to-event by individual country, all countries combined, and in relation to treatment patterns. Finally, between-country variations will be described in relation to 1L treatment patterns and national guidelines. Results: In total, eight countries, Austria, Belgium, Denmark, Finland, Israel, Netherlands, Norway, and Portugal, are included in the study (study flow chart; figure 1 ). Data collection is ongoing and will be finalized by Q1 2021. Inclusion of 120 patients per site will provide precise estimates of local PARPi eligibility (error margin of 4%) and sufficient power to detect clinical meaningful differences in PARPi eligibility between any two countries. Conclusion: International real-world OC data is currently scarce. RESPONSE will add to the current knowledge regarding factors influencing eligibility to 1L PARPi or PARPi + anti-VEGF maintenance treatment in individual countries, and enable mapping of patient characteristics and key variables in the 1L treatment pathway, such as timing and outcome of surgery, including concomitant anti-VEGF treatment. Disclosures: Professor Christian Marth has received funded research from EU, FWF, AstraZeneca and Roche, Honoraria/Expenses from Roche, Novartis, Amgen, MSD, Pharmamar, AstraZeneca, and Tesaro, and has performed Consulting/Advisory Boards for Roche, Novartis, Amgen, MSD, AstraZeneca, Pfizer, Pharmamar, Cerulean, Vertex, and Tesaro. Dr Jacob Korach has nothing to disclose. Dr Kristina Lindemann has acted as Consultant for AstraZeneca, Speaker for AstraZeneca and GSK, and participated in Advisory Boards for AstraZeneca and GSK. Dr Anne Weng Ekmann-Gade has received research grants for the current trial Dr E Van Nieuwenhuysen has nothing to disclose. Dr Heini Lassus has nothing to disclose. Dr Klaus Kaae Andersen is employed by AstraZeneca. Jesper Hansen is employed by AstraZeneca.